Vidas de mulheres : estudo sobre diferentes gerações de mulheres judias brasileiras e australianas - Mühlen, Bruna Krimberg von (2017)
This thesis presents studies that aim to give visibility to Jewish women, as well as deconstruct stereotypes such as associating these women to motherhood (Yiddish Mamma); also break the cycle of persecution that Jewish community has encountered over time. The aim was to understand the identity of Jewish women over three generations, using life history narratives of the participants to observe factors, within their lives cycle, which made these women captive of norms and roles; in three families inserted in the Brazilian culture and three other inserted in the Australian culture. This thesis is composed by four studies. The first one was an essay that aimed to present arguments against and in favor of Jewish women fighting for the same rights as Jewish men. The second study was a systematic review of the literature about Jewish women, gender and feminism, and presented studies found in a research made in the Sydney University’s library database. The third one was qualitative empiric study which worked with the interpretations of the women’s social reality, highlighting the meaning or the phenomenon experienced by them and the importance of social and historic contexts; individual interviews where women told narratives of their life’s sorties were made with nine Jewish women in the south of Brazil, aiming to investigate and understand the construction of their speeches in light of the theory of the conscious space, as well as gender, feminist and systemic theories; the discourse analysis was used searching for the meaning of the speeches. The fourth study was made while I was made during my exchange semester, in Australia. It is a reproduction of the third study, but with nine women from a different culture, Australian, in a country with a similar territorial size and Jewish population (in numbers) as Brazil. Results: It was identified, through the analysis of interviews, that the third generation women benefit from more rights than their grandmas, who encountered more barriers in terms or work and personal life, while second generation women represent a transition of changes acquired in terms of public and private space, having more freedom to make choices, even if that is to maintain old traditions, in both Brazil and Australia. The importance of this research was to give space to Jewish women, who are kept in disadvantage not only because of anti-Semitism, but also within their own religion and culture, due to the influence for the patriarchy in Judaism, where, in orthodox community, Jewish men still hold more power and subjugate the women; while more liberal Jewish females exercise citizenship with more equality and have the freedom to follow their wished with less restrictions and barriers.